Implementasi Pendekatan Saintifik dalam Meningkatkan Pemahaman Peserta Didik di MTs NW Senyiur - Ayatullah Ayatullah; Husnul Laili (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
According to the Ministry of Education and Culture, the scientific approach is a model for student-based learning to be motivated to be more active. The scientific approach is actually not much different from contextual-based learning activities. The knowledge and skills acquired by students are not expected to be the result of remembering a set of facts but are the result of discovering themselves. The scientific approach provides opportunities for students broadly to explore and elaborate on the material they are learning and provides opportunities for students to actualize their abilities through learning activities designed by the teacher. Learning outcomes are conditions that are achieved through learning. In general, everyone can define learning as an effort to improve the behavior of students from knowing to knowing, from not being able to being capable and not being able to be able and so on. From the results of learning can change the behavior and way of thinking of students better and will be stored, attached and not lost in the long term in the lives of students.